Peran Guru Sekolah Minggu dalam Pertumbuhan Iman Anak melalui Pembelajaran Jarak Jauh pada Masa Pandemi Covid-19 - Minarsih Minarsih (DIDAKTIKOS: Jurnal Pendidikan Agama Kristen Duta Harapan, 2021)
Sunday school is a Faith community for the children. In the application of the distance learning system, teachers play an important role in the growth of children's faith. This type of research uses qualitative with a Grounded Theory approach, which means research that develops a series of integrated theoretical concepts from empirical data by combining and interpreting, and showing the relationship of the process. The research was conducted to expand the theory of distance learning ( online) for the growth of children's faith. The results of the research are the building of the following propositions, 1. If the Sunday School teacher is a figure, then his role can't be replaced by technological Sophistication. 2. The moral environment and social community in Sunday school affect children's faith growth. 3. Learning facilities and competence of Sunday school teachers affect the learning conditions of children's faith growth, and 4. Distance Learning ( online) affects the learning outcomes of children's faith growth in Sunday school.  Abstrak Sekolah Minggu merupakan komunitas iman bagi anak. Dalam penerapan sistem pembelajaran jarak jauh guru berperan penting untuk pertumbuhan iman anak. Jenis penelitian menggunakan kualitatif dengan pendekatan grounded theory, yaitu penelitian yang mengembangkan sederet konsep teoritis yang terpadu dari data empiris dengan memadukan dan menginterpretasikan serta memperlihatkan hubungan prosesnya. Penelitian dilakukan untuk memperluas teori pembelajaran jarak jauh (daring) untuk pertumbuhan iman anak. Hasil penelitian adalah bangunan proposisi-proposisi sebagai berikut: (1) jika guru Sekolah Minggu adalah figur, maka perannya tidak tergantikan oleh kecanggihan teknologi, (2) lingkungan moral dan komunitas sosial di Sekolah Minggu berpengaruh pada pertumbuhan iman anak, (3) sarana belajar dan kompetensi guru Sekolah Minggu berpengaruh pada kondisi belajar pertumbuhan iman anak, dan (4) pembelajaran jarak jauh (daring) berpengaruh pada hasil belajar pertumbuhan iman anak di Sekolah Minggu.